Factors Influencing Customers' Decisions To Save At Bengkulu Bank, Manna South Bengkulu Branch - Pabela, Beny; Susanti , Neri; Hidayah , Nenden Restu (Universitas Dehasen Bengkulu, 2025)
This research aims to determine the influence of service quality, interest rates, banking facilities and promotions on customers' decisions to save at Bank Bengkulu, Manna South Bengkulu branch. The sample used in this research was 100 customers who saved at Bank Bengkulu, Manna Bengkulu Selatan branch. Data collection uses a questionnaire and the analysis methods used are validity testing, reliability testing, classical assumption testing, and hypothesis testing. The results of this research show that the value of Y = 0.581 + -0.063 (X1) + 0.197 (X2) + -0.081 (X3) + 0.923 (X4) with a positive regression direction means that service quality has a significant effect on customers' decisions to save, because the significant value is 0.000, which is smaller than 0.05. This means that the quality of service will increase customers' decisions to save at Bank Bengkulu, Manna Bengkulu Selatan branch. Interest rates have a significant effect on customers' decisions to save at Bank Bengkulu Manna South Bengkulu branch because the significant value of 0.000 is smaller than 0.05. This means that the interest rate will increase customers' decisions to save at Bank Bengkulu, Manna Bengkulu Selatan branch. Banking facilities have a significant effect on customers' decisions to save at Bank Bengkulu Manna South Bengkulu branch because the significant value of 0.000 is smaller than 0.05. This means that banking facilities will increase customers' decisions to save at Bank Bengkulu, Manna Bengkulu Selatan branch. Promotion has a significant effect on customers' decisions to save at Bank Bengkulu Manna South Bengkulu branch because the significant value of 0.000 is smaller than 0.05. This means that the promotion will increase customers' decisions to save at Bank Bengkulu, Manna Bengkulu Selatan branch. Service quality, interest rates, banking facilities and promotions have a significant effect on customers' savings decisions so that the initial hypothesis proposed is proven (Ha is accepted). This means that there is a significant influence on service quality, interest rates, banking facilities and promotions on customers' decisions to save together. The coefficient of determination R square is 0.91. This means that service quality, interest rates, banking facilities and promotions influence customers' savings decisions 78% while the remainder (10078% = 22%) is influenced by other causal factors not examined in This study.